Model Supervisi Partisipatif: Integrasi Komite Sekolah dalam Meningkatkan Kompetensi Pedagogik Guru - Idza Irawan; Ahmad Fuad Hasyim Hafid Suyuthi; Maryono (Institut Agama Islam Syubbanul Wathon Magelang, 2026)
This study aims to analyze the role of the principal as a supervisor in improving teachers' pedagogical competence at SDN Sidorejo, Tegalrejo, Magelang. The background of this research is the low pedagogical competence caused by the phenomenon of out-of-field teaching and the gap in academic qualifications of teachers in rural areas. This study uses a descriptive qualitative approach with a case study design. Data were collected through in-depth interviews, non-participant observation, and documentation study, involving the principal, teachers, and the school committee as informants. Data analysis followed the interactive model of Miles, Huberman, and Saldaña. The findings indicate that the principal effectively implements four supervisory roles: 1) as a coordinator by synchronizing administrative policies and external professional networks (KKG); 2) as a consultant through clinical supervision to provide technical solutions for non-linear teachers; 3) as a group leader by fostering a collaborative culture that involves the school committee in curriculum evaluation; and 4) as an evaluator through a diagnostic and solution-oriented weekly reflection process. The study concludes that instructional leadership in rural schools requires an adaptive-directive approach to mitigate teacher qualification limitations. The integration of the school committee in academic supervision provides a new color in strengthening educational accountability at the primary school level.